Pengaruh Penggunaan E-Modul IPA Materi Organ Gerak Hewan dan Manusia Terhadap Hasil Belajar Siswa di SD/MI - Febriani, Agilia; Handini, Nurul; Annisa, Fadillah; Afriani, Nita; A, Armilah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The aim of this research is to understand the impact of implementing E-modules with a focus on animal and human movement organs on student learning achievement in Natural Sciences subjects at elementary school level. The research method used is qualitative with library study data collection techniques. The research results show that the use of the Science E-Module has a positive impact on student learning outcomes. E-Modules help increase student learning motivation, make it easier to understand the material, and accommodate students' individual needs. In addition, science learning using e-modules can function in various forms, such as interactive videos and interesting modules, which reduce student boredom and provide comfort. However, it is necessary to pay attention to issues such as access limitations and excess assumptions over student interests. It is estimated that the use of e-modules in animal and human movement organs is considered effective and innovative, and can increase students' interest in learning and reduce boredom, as well as providing a more real learning experience.